A ninth-year follow-up survey of attitudes and behaviors of obstetricians and gynecologists toward HPV vaccination in Japan - Maki Nakai; Emiko Oka; Yutaka Ueda; Asami Yagi; Tatsuo Masuda; Mamoru Kakuda; Satoshi Nakagawa; Kosuke Hiramatsu; Tadashi Iwamiya; Shinya Matsuzaki; Michiko Kodama (Scientific Reports)
Abstract The Japanese government suspended its proactive recommendation for routine HPV vaccination for nine years, from June 2013 to May 2022, due to concerns about unconfirmed reports of adverse events. This study represents the fifth in our ongoing series of surveys assessing Japanese obstetricians’ and gynecologists’ attitudes toward HPV vaccination, and the first survey conducted since the recommendation was reinstated. In January 2024, we distributed a questionnaire to 632 obstetricians and gynecologists affiliated with Osaka University Hospital. The survey evaluated their attitudes toward HPV vaccination for both daughters and sons. A total of 348 specialists (55.1%) responded. After the government resumed its proactive recommendation, approximately 90% of their daughters had received or planned to receive the HPV vaccine. Among daughters eligible for catch-up vaccination, 71.4% had been vaccinated. Over 70% of respondents agreed that boys should also routinely receive HPV vaccination. Among those with sons aged 12 to 16 at the time of approval for boys, 12.5% had vaccinated them. Most respondents ensured HPV vaccination for their daughters, and some for their sons. Encouraging physicians from other specialties to do the same may help promote widespread HPV vaccine uptake in Japan.